Respiratory system diseases - Pokorski, Mieczyslaw (Springer, 2017)
"Both communicable and noncommunicable diseases of the respiratory system are an increasing healthcare problem despite medical advances. This book aims at unraveling the mechanisms and improving the treatment of pulmonary pathologies, ranging from such common conditions like influenza and related viral infections, functional lung dysfunction, to lung lesions and others. Chapters present late-breaking findings in the diagnostics, pharmacotherapy, and clinical evidence-based decision-making to provide results that can be used to improve healthcare and quality of life. Extending new knowledge and exploring recent medical advances, the book will hopefully help enrich research and clinical experience regarding important respiratory issues. The book is intended for general practitioners and all professionals engaged in the pulmonary field, from basic scientists to clinical investigators"--Publisher's description.
Keywords: Virology.; Respiratory organs -- Diseases.; Neurobiology.; elektronické knihy; electronic books